Financial structure and diversification of European firms - Martina Lawless; Brian O'Connell; Conor O'Toole (The Economic and Social Research Institute (ESRI), 2014)
Small and medium enterprises have been shown to rely mainly on banks for funding and, unlike larger firms, rarely have direct access to capital markets. This paper looks at the extent to which SMEs avail of a wider range of funding options and how their use differs across firms and countries. Using the Survey of Access to Finance in Europe (SAFE) covering sixteen Euro Area countries, we find that firms are currently using two or three sources of finance to fund their firm's operations and have had previous experience of other types of funding. There are some noticeable differences across countries with funding types in peripheral economies generally being less diversified. Differences across firm size and age groups are more marked than cross-country variation, with smaller and younger firms significantly more reliant on a limited set of finance types and older, larger firms having more diversified financial structures. Looking at individual sources of financing, we find that trade credit and informal sources of finance are extremely prevalent across all countries, with Irish firms being particularly likely to use them as sources of funding.
Keywords: 330; KMU; Unternehmensfinanzierung; Eurozone